Methodologies for evaluating the marginal cost of reducing greenhouse gas emissions in decarbonization: a systematic review - Morila, Thiago Senatore; Reis Junior, Neyval Costa (Brazilian Journal of Production Engineering, 2025)
This is a review of methodologies that use the marginal abatement cost (MAC) of greenhouse gas emissions, with the aim of identifying the types of approaches available, their advantages, disadvantages, in which cases they are used and how complex they are (both computationally and in terms of obtaining data). The results of the research found and explained six main types of models: expert-based approaches, engineering models, distance functions, computable general equilibrium models, integrated assessment models and hybrid models in which all use MAC curves to identify economic measures to mitigate climate change and establish decarbonization pathways. In addition, the possibility of using hybrid models that integrate various methodologies for a more complete assessment is discussed, as well as the difficulties of applying them. The main contribution is not only to provide a review of the methodologies, but also to compare them and show in which contexts each one is best applied, seeking to serve as a guide for future research and practical applications in environmental economics.
Keywords: Marginal abatement cost curves; Greenhouse Gas Mitigation; Review of Methodologies; Environmental Economics